Concurrent radiotherapy for patients with metastatic melanoma and receiving anti-programmed-death 1 therapy: a safe and effective combination. Issue 5 (October 2017) - Aboudaram, Amélie; Modesto, Anouchka; Chaltiel, Léonor; Gomez-Roca, Carlos; Boulinguez, Serge; Sibaud, Vincent; Delord, Jean-Pierre; Chira, Ciprian; Delannes, Martine; Moyal, Elizabeth; Meyer, Nicolas
Abstract : A combination of immune-checkpoint inhibitors and radiation therapy (RT) represents a promising therapeutic strategy in part mediated by the abscopal effect, but clinical experience related to this combination remains scarce. Clinical data and patterns of treatment were retrospectively collected from all consecutive patients with metastatic melanoma and receiving programmed-death 1 (PD-1) immune-checkpoint inhibitors. Survival data, best overall response, and acute and delayed toxicities (graded according to Common Terminology Criteria for Adverse Events, v 4.3) were compared between patients receiving concurrent RT (IR) or no irradiation (NIR). Fifty-nine patients received anti-PD-1 immunotherapy [pembrolizumab ( n =28) or nivolumab ( n =31)] between August 2014 and December 2015 at our institution. Among these, 29% ( n =17) received palliative RT for a total of 21 sites, with a mean dose of 30 Gy delivered in 10 fractions. Acute and late toxicity profiles were similar in the two groups. After a 10-month median follow-up, the objective response rate (complete or partial response) was significantly higher in the IR group versus the NIR group (64.7 vs. 33.3%, P =0.02) and one complete responder after RT was compatible with an abscopal effect. The 6-month disease-free survival and overall survival rates for the NIR group versus the IR group were 49.7 versus 64.7% ( P =0.32) and 58.8 versus 76.4% ( P =0.42), respectively. We report here that the combination of RT and anti-PD-1 immunotherapy is well tolerated and leads to a significant higher tumor response rate within and outside the irradiated field, which is emphasized by the first reported case of an abscopal effect in solid tumors.